2010
DOI: 10.1248/bpb.33.321
|View full text |Cite
|
Sign up to set email alerts
|

Glycyrrhetinic Acid Induces Anoikis-Like Death and Cytoskeletal Disruption in the Central Nervous System Tumorigenic Cells

Abstract: Licorice extracts and the principal licorice component glycyrrhizin (GL) are used worldwide in foods, tobacco and medicines. The sweet taste of licorice roots arises from GL, which is reputed to be at least 50 times sweeter than refined sugar. Owing to this sweetness, GL is extensively used as a natural sweetener and flavoring additive.1) GL is a saponin compound comprising a triterpenoid aglycone, glycyrrhetinic acid (GA), conjugated to a disaccharide of glucuronic acid. GA is used as an antitoxic and immunol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…Rare causes of apparent mineralocorticoid excess include the genetic deficiency of 11- β -HSD2, sometimes present in adulthood, which although usually appears in childhood, it is often asymptomatic and may stay undiagnosed until adulthood [ 229 ]. An in vitro evaluation demonstrated that glycyrrhetinic acid in humans at relevant concentrations may disturb cell adhesion, effect anoikis-like cell death, cause morphologic changes, and disturb cytoskeletal proteins [ 230 ].…”
Section: Toxicological Data Safety and Bioavailability Featuresmentioning
confidence: 99%
“…Rare causes of apparent mineralocorticoid excess include the genetic deficiency of 11- β -HSD2, sometimes present in adulthood, which although usually appears in childhood, it is often asymptomatic and may stay undiagnosed until adulthood [ 229 ]. An in vitro evaluation demonstrated that glycyrrhetinic acid in humans at relevant concentrations may disturb cell adhesion, effect anoikis-like cell death, cause morphologic changes, and disturb cytoskeletal proteins [ 230 ].…”
Section: Toxicological Data Safety and Bioavailability Featuresmentioning
confidence: 99%
“…The proliferative inhibition of vinblastine in P-glycoprotein-overexpressing human carcinoma KB-C2 and doxorubicin in KB/MDR cells are also enhanced with the combined treatment of GA [87]. Others: GA induces anoikis-like cell death and disturbs cytoskeletal protein expression in central nervous system tumorigenic cells [88]. In NSCLC cells, GA inhibits cell proliferation by inhibiting the activity of the thromboxane synthase protein, which is overexpressed in NSCLC and carries a poor prognosis [89].…”
Section: Glycyrrhetinic Acidmentioning
confidence: 99%
“…Ras pathways have been targeted for the development of chemotherapeutic interventions against tumor cells by interfering with cytoskeletal proteins such as actin (31) and tubulin (43). Furthermore, in our previous (44,45) and current studies, we found that GA disrupted F-actin and ␤III-tubulin, which could lead to loss of functionality for cell growth or proliferation and result in apoptosis of the cells. These findings indicate that disturbances in cytoskeletal proteins may be the factors involved in the toxic effects of GA against the tumor cells.…”
Section: Discussionmentioning
confidence: 55%